(untitled) - FAO Fisheries Department (Rome, 2000)
The book continues to be to provide policy-makers, civil society and those who derive their livelihood from the sector a comprehensive, objective and global view of capture fisheries and aquaculture, including associated policy issues.
Keywords: Agriculture and state,Fisheries; Economic aspects